2013
DOI: 10.1097/mib.0b013e31828075a7
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Osteoporosis in Crohnʼs Disease

Abstract: Low body mass index, early disease onset, high corticosteroid doses and, anti-tumor necrosis factor α therapy are associated with increased risk of osteoporosis. Lower T scores in patients on infliximab occur as patients receiving this therapy have more severe inflammation, which is associated with elevated osteoclastogenic factors, rather than as a side-effect of the anti-tumor necrosis factor-α therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 53 publications
(58 reference statements)
1
7
0
1
Order By: Relevance
“…The third main finding in our study is that low BMI was a risk factor for reduced BMD, which matches data from previous studies[ 17 , 29 , 30 ]. This finding was more evident in CD patients than in UC patients; BMI could predict the severity of reduced BMD with a sensitivity of 77% and a specificity of 63%, AUC 0.73 (95%CI: 0.59–0.84) in the CD group.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The third main finding in our study is that low BMI was a risk factor for reduced BMD, which matches data from previous studies[ 17 , 29 , 30 ]. This finding was more evident in CD patients than in UC patients; BMI could predict the severity of reduced BMD with a sensitivity of 77% and a specificity of 63%, AUC 0.73 (95%CI: 0.59–0.84) in the CD group.…”
Section: Discussionsupporting
confidence: 92%
“…For our study, this result may be due to the lack of a registry to precisely record our patients’ steroid therapy details. Intake of prednisolone > 7.5 mg/d for 3 mo is an established risk for developing osteoporosis[ 33 ], as shown in previous studies[ 17 , 27 , 30 ].…”
Section: Discussionmentioning
confidence: 89%
“… 32 Multiple studies have also demonstrated an increased risk of serious infection, opportunistic infection, osteoporosis, morbidity, and mortality associated with steroid use in IBD. 6 , 33 , 34 Therefore, the older patients likely represent the most at-risk IBD subgroup for steroid-associated complications; however, maintenance steroid therapy seems to be more commonly prescribed over the steroid-sparing immunomodulators and biologics.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking,8 obesity,9 chronic renal failure,10 hyperthyroidism,11 rheumatoid arthritis,12 inflammatory bowel diseases13 are well known to be associated with osteoporosis and have been reported on extensively. Obesity as a protective factor has already been reported 14.…”
Section: Discussionmentioning
confidence: 99%